Drosophila Females Undergo Genome Expansion after Interspecific Hybridization - Romero-Soriano, Valèria (Genome Biol Evol, 2016)
Genome size (or C-value) can present a wide range of values among eukaryotes. This variation has been attributed to differences in the amplification and deletion of different noncoding repetitive sequences, particularly transposable elements (TEs). TEs can be activated under different stress conditions such as interspecific hybridization events, as described for several species of animals and plants. These massive transposition episodes can lead to considerable genome expansions that could ultimately be involved in hybrid speciation processes. Here, we describe the effects of hybridization and introgression on genome size of Drosophila hybrids. We measured the genome size of two close Drosophila species, Drosophila buzzatii and Drosophila koepferae, their F(1) offspring and the offspring from three generations of backcrossed hybrids; where mobilization of up to 28 different TEs was previously detected. We show that hybrid females indeed present a genome expansion, especially in the first backcross, which could likely be explained by transposition events. Hybrid males, which exhibit more variable C-values among individuals of the same generation, do not present an increased genome size. Thus, we demonstrate that the impact of hybridization on genome size can be detected through flow cytometry and is sex-dependent.